Intraindividual comparison between (68)Ga-PSMA-PET/CT and mpMRI for intraprostatic tumor delineation in patients with primary prostate cancer: a retrospective analysis in 101 patients - Spohn, Simon (Eur J Nucl Med Mol Imaging, 2020)
PURPOSE: Accurate delineation of intraprostatic gross tumor volume (GTV) is mandatory for successful fusion biopsy guidance and focal therapy planning of prostate cancer (PCa). Multiparametric magnetic resonance imaging (mpMRI) is the current gold standard for GTV delineation; however, prostate-specific membrane antigen positron emission tomography (PSMA-PET) is emerging as a promising alternative. This study compares GTV delineation between mpMRI and (68)Ga-PSMA-PET in a large number of patients using validated contouring approaches. METHODS: One hundred one patients with biopsy-proven primary PCa who underwent mpMRI and (68)Ga-PSMA-PET within 3 months before primary treatment were retrospectively enrolled. Clinical parameters (age, PSA, Gleason score in biopsy) were documented. GTV based on MRI and PET images were delineated; volumes measured and laterality determined. Additionally, biopsy data from 77 patients was analyzed. Univariate and multivariate binary logistic regression analyses were performed using concordance in laterality as the endpoint. RESULTS: In total mpMRI and (68)Ga-PSMA-PET detected 151 and 159 lesions, respectively. Median GTV-MRI (2.8 ml, 95% CI 2.31–3.38 ml) was significantly (p < 0.0001) smaller than median GTV-PET (4.9 ml, 95% CI 3.9–6.6 ml). (68)Ga-PSMA-PET detected significantly more bilateral lesions than mpMRI (71 vs 57, p = 0.03). Analysis of patients with bilateral lesions in biopsy showed a significant higher concordance of laterality in (68)Ga-PSMA-PET (p = 0.03). In univariate analysis, PSA level and volume of GTV-MRI had an impact on concordance in laterality (p = 0.02 and p = 0.01), whereas in multivariate analysis, only GTV-MRI volume remained significant (p = 0.04). CONCLUSION: MpMRI and (68)Ga-PSMA-PET detect a similar amount of PCa lesions. However, GTV-PET had approximately twice the volume (median 4.9 ml vs 2.8 ml) and detected significantly more bilateral lesions than mpMRI. Thus, (68)Ga-PSMA-PET gives highly important complementary information. Since we could not find any strong evidence for parameters to guide when (68)Ga-PSMA-PET is dispensable, it should be performed additionally to MRI in patients with intermediate and high-risk PCa according to D’Amico classification to improve GTV delineation.